2022
DOI: 10.3389/fpls.2022.983460
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes in the transcriptome landscape of Arabidopsis thaliana in response to cold stress

Abstract: Plants must reprogram gene expression to adapt constantly changing environmental temperatures. With the increased occurrence of extremely low temperatures, the negative effects on plants, especially on growth and development, from cold stress are becoming more and more serious. In this research, strand-specific RNA sequencing (ssRNA-seq) was used to explore the dynamic changes in the transcriptome landscape of Arabidopsis thaliana exposed to cold temperatures (4°C) at different times. In total, 7,623 different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 124 publications
0
5
0
Order By: Relevance
“…It is considerably downregulated in dss1(V) mutants. According to different studies, this gene is involved in the removal of H 2 O 2 , the biosynthesis and degradation of lignin, the response to environmental stresses, pathogen attack, and oxidative stress [ 40 ]. However, it remains unproven whether the regulation of PRX70 enzyme transcription could be directly influenced by DSS1(V).…”
Section: Discussionmentioning
confidence: 99%
“…It is considerably downregulated in dss1(V) mutants. According to different studies, this gene is involved in the removal of H 2 O 2 , the biosynthesis and degradation of lignin, the response to environmental stresses, pathogen attack, and oxidative stress [ 40 ]. However, it remains unproven whether the regulation of PRX70 enzyme transcription could be directly influenced by DSS1(V).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that low temperature alters the expression of lncRNAs and mRNAs in plants and animals [24][25][26][27]. When Enshi black pigs were exposed to low temperatures, acute cold stress-induced more DElncRNAs and response pathways compared to cold acclimation.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, 135 differentially expressed lncRNAs have been identified in the early stages of cold treatment in Arabidopsis (Calixto et al, 2019). Applying more rigorous filtering for noncoding potential, another recent study identified 114 novel lncRNAs on 86 loci (Liu, Cai, et al, 2022). While it remains to be tested how many of (Heo & Sung, 2011;Kim & Sung, 2017;Swiezewski et al, 2009).…”
Section: Long Noncoding Rnas (Lncrnas) In the Regulation Of Cold Resp...mentioning
confidence: 99%
“…Perception of cold, both as a stress and cue for development, triggers signalling cascades that converge in the nucleus in a dynamic reprogramming of the plant transcriptome. Interestingly, numerous A. thaliana genes are either responsive to short‐term (timescale of hours) or long‐term (timescale of months) cold treatments (Calixto et al, 2018; Fowler & Thomashow, 2002; Li et al, 2021; Liu, Cai, et al, 2022; Xi et al, 2020). Although most transcriptomic studies have so far measured steady‐state RNA (messenger RNA [mRNA]) levels, recent developments are allowing monitoring of the dynamics of the nascent transcriptome in response to cold (Kindgren et al, 2019).…”
Section: Molecular Mechanisms Underlying Cold Stress and Developmenta...mentioning
confidence: 99%
See 1 more Smart Citation